(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
A general corpus may include written or spoken texts, or a selection of texts from both media. Recently, we have seen an increase in the number of spoken corpora due to improvements in writing technologies and automated transcription software. linguists have created synchronic corpora to track language change and language change in corpus data, primarily to provide a "snapshot" of language use at a specific point or time period. The monitor case differs from the others presented here in the sense that it is constantly growing (dynamic) with the addition of new materials. Corpora constructed for a linguistic account of a language in time usually contain texts representing language use in different periods of the language under investigation.